prove that d/dx (cscx) = -cscxcotx

how do i prove this?

Printable View

- Sep 25th 2012, 03:05 PMpnfullerDerivative PROOFS
prove that d/dx (cscx) = -cscxcotx

how do i prove this? - Sep 25th 2012, 03:11 PMMarkFLRe: Derivative PROOFS
I would begin with:

$\displaystyle \frac{d}{dx}(f(x))\equiv\lim_{h\to0}\frac{f(x+h)-f(x)}{h}$ - Sep 25th 2012, 03:12 PMskeeterRe: Derivative PROOFS
$\displaystyle \csc{x} = (\sin{x})^{-1}$

use the chain rule ...

or

$\displaystyle \csc{x} = \frac{1}{\sin{x}}$

use the quotient rule ...